2005
DOI: 10.1002/jso.20407
|View full text |Cite
|
Sign up to set email alerts
|

Non-axillary breast cancer recurrences after sentinel node biopsy

Abstract: The incidence of nodal recurrences outside the axilla is low. Although all extra-axillary sentinel nodes were pursued, some of these recurrences concern missed sentinel nodes that harbor metastasis. Identification of all sentinel nodes and subsequent treatment of the involved basins may reduce the risk of breast cancer recurrences in these unusual locations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Such recurrences are rare and most commonly followed by distant metastasis (11 of 14 patients in the present study). It could be debated whether extra‐axillary nodal recurrence should be viewed as the consequence of a false‐negative SNB finding or as a secondary aberrant primary drainage pattern; however, as this is an rare event, an answer is difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…Such recurrences are rare and most commonly followed by distant metastasis (11 of 14 patients in the present study). It could be debated whether extra‐axillary nodal recurrence should be viewed as the consequence of a false‐negative SNB finding or as a secondary aberrant primary drainage pattern; however, as this is an rare event, an answer is difficult to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, all 3 IMLN recurrent patients (0.6%) underwent chemo-radiation therapy. van Rijk et al [16] explained that the failure of extra-axillary SLN biopsy is the cause of extra-axillary nodal recurrence of breast cancer. These authors also found that all IMLN metastasis developed 24, 46, and 63 months after surgery.…”
Section: Discussionmentioning
confidence: 99%